An Investigation of Patterns and Factors Associated with Exclusive Breast Feeding in Northern Ghana - Saaka, Mahama; Takyi, Solomon Addae; Maxwell, Tetteh (International Journal of Child Health and Nutrition, 2013)
Introduction: The main aim of this study was to assess the practice of exclusive breastfeeding (EBF) and explore its determinants in Tamale Metropolis, Northern Ghana. Methods: In this analytical cross-sectional study, systematic random sampling was used to select 355 mother- infant pairs between 0-6 months from among consenting mothers attending post natal care at the Tamale Teaching and West Hospitals in the Tamale Metropolis. Results: The prevalence of EBF among infants < 6 months in the Tamale Metropolis for the past 24 hours was 92.1 % but it was 75.5 % in the one month prior to the study. In logistic regression analyses, factors that had significant positive association with EBR were institutional delivery, current mother’s employment, maternal motivation and household wealth index. Compared to home delivery, women who delivered at a health institution were five times more likely to practice EBF (Adjusted odds ratio [AOR] = 5.17, CI: 2.45 – 10.90). Petty traders were four times more likely to exclusively breastfeed, compared to women who were unemployed (A OR = 4.05, CI: 1.93 – 8.51). EBF provided 80 % (Adjusted OR = 0.2, CI: 0.08-0.37) protection against chronic malnutrition whilst high household index reflecting socio-economic status provided only 10 % protection against chronic malnutrition in the study sample (Adjusted OR = 0.9, CI: 0.81- 0.98). Conclusion and Recommendation: Strategies that target improving knowledge and skills on lactation management among women, as well as strategies to improve health facility delivery especially among non-working mothers, may help to improve EBF in Northern Ghana.